Sentence Repetition as a Tool for Screening Morphosyntactic Abilities of Bilectal Children with SLI - Theodorou, Elena; Kambanaros, Maria; Grohmann, Kleanthes K. (Frontiers in Psychology, 2017)
The clinical significance of sentence repetition tasks (SRTs) for assessing children's language ability is well-recognized. SRT has been identified as a good clinical marker for children with (specific) language impairment as it shows high diagnostic accuracy levels. Furthermore, qualitative analysis of repetition samples can provide information to be used for intervention protocols. Despite the fact that SRT is a familiar task in assessment batteries across several languages, it has not yet been measured and validated in bilectal settings, such as Cypriot Greek, where the need for an accurate screening tool is urgent. The aims of the current study are three-fold. First, the performance of a group of (Cypriot) Greek-speaking children identified with SLI is evaluated using a SRT that elicits complex morphosyntactic structures. Second, the accuracy level of the SRT for the identification of SLI is explored. Third, a broad error analysis is carried out to examine and compare the morphosyntactic abilities of the participating children. A total of 38 children aged 5–9 years participated in this study: a clinical group of children with SLI (n = 16) and a chronological age-matched control group (n = 22). The ability of the children to repeat complex morphosyntactic structures was assessed using a SRT consisting of 24 sentences. The results showed that the SRT yielded significant differences in terms of poorer performance of children with SLI compared to typically developing peers. The diagnostic accuracy of the task was validated, since regression analysis showed that the task is sensitive and specific enough to identify children with SLI. Finally, qualitative differences between children with SLI and those with TLD regarding morphosyntactic abilities were detected. This study showed that a SRT that elicits morphosyntactically complex structures could be a potential clinical indicator for SLI in Cypriot Greek. The task has the potential to be used as a referral criterion in order to identify children whose language needs to be evaluated further. Implications for speech–language therapists and policy-makers are discussed.